Mental Health in Context: Sociodemographic Differences in Mental Health Knowledge, Attitudes, Behaviour, and Diagnosis in South Africa - Stephanie Alcock; Michelle Leal; Johanna Beukes; Urlridge Thompson; Shane A. Norris (South African Journal of Psychology, 2026)
Knowledge, attitudes, and behaviours (KAB) influence mental health outcomes and vary across sociodemographic groups. In South Africa, where there is a high burden of mental health conditions, it is important to understand these factors to inform public health strategies. This study examined (a) group differences in mental health KAB and diagnosis; (b) associations between sociodemographic factors, KAB, and mental health diagnosis; and (c) whether mental health literacy (MHL), self-stigma, and help-seeking mediate the relationship between socioeconomic status (SES) and diagnosis. We collected data from 1,000 South African adults (aged 18–65) using a cross-sectional online survey. Chi-square and Kruskal–Wallis tests were used to assess group differences, while logistic regression and generalised structural equation modelling (GSEM) were used to examine direct and indirect associations. Higher SES, tertiary education, and employment were associated with greater MHL, reducing stigma, and increasing help-seeking, and a dual burden of health-promoting and risk behaviours. Higher-status groups more often endorsed evidence-based risk and treatment, whereas lower-status groups and men favoured traditional or spiritual explanations. Having a mental health diagnosis was associated with chronic conditions (odds ratio [ OR ] = 2.70, p < .001), perceived stress ( OR = 3.64, p < .001), alcohol use ( OR = 1.53, p = .015), and drug use ( OR = 2.04, p = .002). Higher SES was associated with greater MHL (β = 1.48, p < .001), reducing stigma (β = −0.78, p < .001), and increasing help-seeking (β = 0.12, p = .001). Strategies focused on improving mental health outcomes should address not only MHL and stigma but also Socioeconomic conditions that shape KAB.